Consolidating the principles of social responsibility and its role in achieving sustainable in Algerian telecommunications companies (Jeezy Ooredoo Mobilis) - Nawel, Attoui (International journal of economic perspectives, 2024)
This study aims to highlight the importance of adopting social responsibility in companies and the extent of its contribution to supporting the dimensions of sustainable development, by presenting the experiences of Algerian telecommunications companies (jazzy; ooredoo; mobilis), which demonstrated the company’s commitment to applying the principles of social responsibility, activating their social role and increasing their ability to respond to environmental changes. Ministry of foreign affairs, as it concluded that the practice of social responsibility reflects positively on improving and enhancing the reputation of the institution on the one hand, and on serving the community on the other hand, and also contributes to improving the requirements of sustainable development. The study recommended the necessity of integrating programs concerned with social responsibility within future visions of economic institutions.